COLORS IN MEDIEVAL BOOK PICTURES AND MINIATURES: मध्यकालीन पुस्तक चित्रो तथा लघु चित्रो में रंग - Kumar Tiwari, Pawanendra (International Journal of Research -GRANTHAALAYAH, 2014)
In medieval India, colors for drawing were obtained from a variety of substances such as minerals, compounds or natural salts. Some colors were derived from natural materials such as plant biomass. For example, neem and wormwood etc. were used in large scale not only in pictures but also in writing. Similarly, because of red ink written in silver and gold, Swanakshari Shetakshari was named. Red ink was used to draw margins at the end of the prominence, in the lines, in the instruments, etc. Books written with gold and silver powder were more expendable and they had more sense of grandeur. It was also relatively difficult to write the letters of silver and gold and in reading it there was a lot of emphasis on the eyes. Most of the mineral colors have been used in the West Indian painting style. These were finely powdered and brought into color. The natural state of the dyes was impure, so it was purified by dissolving it in water. Heavy impurities used to sit at the bottom and the top water was drained and separated. This process was repeated many times and color refinement was used to dry it and used it for illustration. This action was called color washing. मध्यकालीन भारत में चित्रण के लिए रंग कई प्रकार के पदार्थो जैसे खनिजों योगिको अथवा प्राकृतिक लवणों से प्राप्त किये जाते थे। कुछ रंग प्राकृतिक वस्तुओं जैसे वनस्पति जैव पदार्थो से प्राप्त किये जाते थे। उदाहरण के लिए नीम तथा कृमिदाना आदि काजल का प्रयोग न केवल चित्रो में बल्कि लेखन कार्य में भी बडे पैमाने पर हुआ। इसी प्रकार लाल स्याही चाँँदी तथा सोने में लिखा होने के कारण स्वणाक्षरी शेत्याक्षरी नाम दिया गया । लाल स्याही का प्रयोग अहमायो के अन्त में हाशिये खीचने में वृन्तों रेखाओं यंत्रों आदि में हुआ। स्वर्ण रजत चूर्ण से लिखी जाने वाली पुस्तके अधिक व्यय-साध्य थी उनमें वैभव-प्रदर्शन की भावना अधिक होती थी। चाँदी तथा स्वर्ण के अक्षरों को लिखना भी अपेक्षाकृत कठिन होता था तथा उसको पढने में भी आखो पर अधिक जोर पडता था। पश्चिम भारतीय चित्र-शैली में अधिकतर खनिज रंगों का प्रयोग किया गया है। इन्हें बारीक चूर्ण के रूप में लाकर रंग बनाया जाता था। रंगो की प्राकृतिक अवस्था अशुद्ध होती थी अतः उसको पानी में घोलकर निथारकर शुद्ध किया जाता था। भारी अशुद्धियाँ नीचे बैठ जाती थी तथा ऊपर का पानी निथारकर पृथक् कर लिया जाता था। इस क्रिया को कई बार दोहराकर रंग का शोधन किया जाता था इसे सुखाकर चित्रण-कार्य में प्रयुक्त करते थे। इस क्रिया को रंग धोना कहते थे।